PENERAPAN METODE IQRA’ DALAM MENINGKATKAN PEMAHAMAN MEMBACA AL-QUR’AN PADA PESERTA DIDIK DI KELAS III MIS AL-MUHAJIRIN PALUKECAMATAN PALU BARAT KOTA PALU - Adhim, Fauzul; Anirah, Andi; Hamdani, Fikri (IBTIDAI'Y DATOKARAMA: JURNAL PENDIDIKAN DASAR, 2025)
The purpose of this study was to determine the application of the Iqra method in improving students' understanding in reading the Qur'an, as well as the individual abilities of students in reading the Qur'an. The research method in this thesis is to use a qualitative approach, this study uses observation data collection techniques, interviews, and documentation which are analyzed using data reduction, data presentation and drawing conclusions. The results of this study are the application of the Iqra method in class III MIs Al-Muhajirin Palu active in learning, can be seen from the steps of implementing the Iqra method, namely: 1. Planning, the teacher prepares the process of compiling lesson materials using teaching media. 2. Implementation, divided into three components: initial activities, activities carried out before starting the learning process. core activities, the main activities in the learning process carried out by the teacher and students. and final activities, closing activities are activities carried out at the end of learning. 3. Evaluation, the process of collecting and analyzing student learning outcome data. This evaluation is carried out to determine the extent to which learning objectives have been achieved. It can be concluded that the application of the Iqra method in class III of Al-Muhajirin Palu Elementary School is taught in the subject (BTA) of reading and writing the Qur'an, in learning to read and write the Qur'an the teacher uses the Iqra book as a reference and basis for improving students' understanding of reading the Qur'an and also uses the Juz Amma book for students who have completed their Iqra book from volume 1 to volume 6.